New Wistar Kyoto and spontaneously hypertensive rat transgenic models with ubiquitous expression of green fluorescent protein - Ana Isabel Garcia Diaz; Ben Moyon; Philip M. Coan; Neza Alfazema; Lara Venda; Kevin Woollard; Tim Aitman (The Company of Biologists, 2016)
The Wistar Kyoto (WKY) rat and the spontaneously hypertensive (SHR) rat inbred strains are well-established models for human crescentic glomerulonephritis (CRGN) and metabolic syndrome, respectively. Novel transgenic (Tg) strains add research opportunities and increase scientific value to well-established rat models. We have created two novel Tg strains using Sleeping Beauty transposon germline transgenesis, ubiquitously expressing green fluorescent protein (GFP) under the rat elongation factor 1 alpha (EF1a) promoter on the WKY and SHR genetic backgrounds. The Sleeping Beauty system functioned with high transgenesis efficiency; 75% of new rats born after embryo microinjections were transgene positive. By ligation-mediated PCR, we located the genome integration sites, confirming no exonic disruption and defining a single or low copy number of the transgenes in the new WKY-GFP and SHR-GFP Tg lines. We report GFP-bright expression in embryos, tissues and organs in both lines and show preliminary in vitro and in vivo imaging data that demonstrate the utility of the new GFP-expressing lines for adoptive transfer, transplantation and fate mapping studies of CRGN, metabolic syndrome and other traits for which these strains have been extensively studied over the past four decades.